A model of preliminary breakdown pulse peak currents and their relation to the observed electric field pulses. Issue 1 (13th January 2017) - Kašpar, Petr; Santolík, Ondřej; Kolmašová, Ivana; Farges, Thomas
Abstract: Preliminary breakdown pulses (PBPs) occur in the initial phase of lightning. A realistic model for their description is employed to investigate relation between PBP peak currents and PBP electric field amplitudes and their relation to the return stroke (RS) peak currents. We demonstrate that the PBP peak currents can reach 200 kA and can be comparable or higher than the corresponding RS peak currents. For a typical PBP electric field waveform PBP peak currents are approximately proportional to the electric field amplitudes. We show that the PBP bipolar overshoot depends primarily on the characteristic time of the line conductivity increase. The magnitude of the charge centers is demonstrated to be very large in order to model the observed PBPs with amplitudes up to 32 V/m at 100 km. Such energetic current pulses might be capable to produce elves or terrestrial gamma ray flashes. Key Points: A physics‐based model for a predefined charge layer structure in the thundercloud is developed Peak currents linked to the preliminary breakdown pulses are found to be approximately proportional to their electric field peak amplitudes Modeled preliminary breakdown currents are found to reach 200 kA and are comparable to the peak currents of the corresponding return strokes